FUNDAMENTAL STUDY OF THE EFFECT OF IRON REDUCTION ON THE BINDER TYPE IN IRON ORE BRIQUETTE - Khairil, .; Mahidin, .; Iskandar, . (MATTER: International Journal of Science and Technology, 2015)
As well known that the Iron and Steel Industry has been priority policy by the Indonesian government in order to meet the requirement of iron and steel in community base. There were made to develop processes for producing iron for steelmaking that could serve as alternatives and/or supplements to the conventional blast furnace in order to produce both of them save energy, low cost, and environmentally friendly. Fundamental study on the effect of the iron reduction on binder type in iron ore briquette was studied by using an electric furnace. In the experiments, three types of samples were used. The iron ore was mixture by using low-grade coal and three kinds of binder for making iron ore briquette. The CO2 and N2 gas based were injected into the reduction as the reducing gas media. The reduction degree properties were expressed in terms of iron ore reduction index (IRI). The iron ore reduction index was determined by the mass change of the sample after reduced with CO2 as gas media. The reduction degree iron in the sample was characterized by using X-ray diffraction (XRD) analysis. The experimental results show that low-grade coal content and binder type are playing an important role in briquette mass reduction. The mass reduction of iron ore briquette composed of 10 % low-grade coal is faster compared to that composed without using low-grade coal. The briquette by using heavy oil as a binder that higher mass reduction is obtained. The component in the sample was dominated by Fe2O3, Fe3O4 and carbon It was shown that iron ore briquette by using asphalt as binder reduced of Fe2O3 into Fe3O4 easily than that using heavy oil and bentonite.